Pengembangan desain kursi new normal untuk fasilitas duduk publik - Gracia Vita Kurniawan; Grace Mulyono; Taufan Rizqy (Institut Seni Indonesia Yogyakarta, 2022)
Entering the new normal era, people need safe and comfortable public space seating facilities. Most of the existing public facilities are sufficient for the new normal era, but only a cross on the actual seat can still be used. Seeing these problems, the research was carried out with the aim of producing a new normal sitting facility with a modular and compact form, able to provide viruses, and provide users with protection from COVID-19. This study uses the Stanford D.School